Isotope ratio laser spectroscopy to disentangle xylem-transported from locally respired CO2 in stem CO2 efflux. (6th February 2019) - Salomón, Roberto L; De Roo, Linus; Bodé, Samuel; Boeckx, Pascal; Steppe, Kathy
Abstract: Respired CO2 in woody tissues radially diffuses to the atmosphere or it is transported upward with the transpiration stream, making the origin of CO2 in stem CO2 efflux ( E A ) uncertain, which may confound stem respiration ( R S ) estimates. An aqueous 13 C-enriched solution was infused into stems of Populus tremula L. trees, and real-time measurements of 13 C-CO2 and 12 C-CO2 in E A were performed via Cavity Ring Down Laser Spectroscopy (CRDS). The contribution of locally respired CO2 ( L CO2 ) and xylem-transported CO2 ( T CO2 ) to E A was estimated from their different isotopic composition. Mean daily values of T CO2 / E A ranged from 13% to 38%, evidencing the notable role that xylem CO2 transport plays in the assessment of stem respiration. Mean daily T CO2 / E A did not differ between treatments of drought stress and light exclusion of woody tissues, but they showed different T CO2 / E A dynamics on a sub-daily time scale. Sub-daily CO2 diffusion patterns were explained by a light-induced axial CO2 gradient ascribed to woody tissue photosynthesis, and the resistance to radial CO2 diffusion determined by bark water content. Here, we demonstrate the outstanding potential of CRDS paired with 13 C-CO2 labelling to advance in the understanding of CO2 movement at the plant−atmosphere interface and the respiratory physiology in woody tissues.